Tannase Production from Bacillus amyloliquefaciens in Submerged Fermentation Through Response Surface Methodology: Tannase Production from Bacillus amyloliquefaciens - Hafiz Abdullah Shakir; Iqra Javed; Muhammad Irfan; Shaukat Ali; Muhammad Khan; Javed Iqbal Qazi; Muhammad Abrar Yousaf (Biological Sciences - PJSIR, 2022)
Tannase (Tannin acyl hydrolase) is an intracellular/extracellular enzyme produced by micro- organisms. Tannase has high market demand due to its important role in different industries. The optimization of different parameters for each micro-organism is necessary for obtaining maximum tannase yield. The aim of present study was to optimize the medium components and their concentration employing applications of response surface methodology (RSM). Ten bacterial strains isolated from fish gut content were screened for tannase producing potential. Among these, four strains, Klebsiella oxytoca, Roultella ornithinolytica, Bacillus amyloliquefaciens and Enterobacter aerogenes expressed greenish zones around their colonies. amyloliquefaciens showed highest tannase production (1.27 lU/mL) under un-optimized conditions and was selected for further work. During one factor at a time optimization of physical parameters, incubation temperature 37 °C, pH 5, inoculum size 1% and incubation period of 24 h yielded maximum tannase. To screen the significant medium components, 12 experimental runs of Plackett-Burman design for six variables (tannic acid, K2HP04, CaCl2, MgS04, NH4N03 and yeast extract) were carried out. From these experimental runs, the enzyme assay results were analyzed using multiple regression. Three variables i.e., tannic acid, CaCl2 and yeast extract showed significant impact on tannase production. Concentrations of these variables were optimized using Box-Behnken design (BBD). Results of 15 experimental runs of BBD showed maximum tannase production corresponding to 0.5% tannic acid, 0.1% CaCl2 and 0.275% yeast extract. The highest tannase activity was recorded at pH 7, 0.5% substrate concentration and 40 °C.